Development of low-fat frozen yoghurt incorporated with strawberry and beetroot powder - Patel, Dhaval; Dharaiya, Chetan N; Patel, Dhinal; Patel, Amit (Indian Journal of Dairy Science, 2024)
Low-fat frozen yoghurt was prepared using a blend of strawberry and beetroot powder as one of the ingredients. Response surface methodology (RSM) was used to optimize the level of strawberry and beetroot powder, stabilizer-emulsifier mixture and sugar. The responses were sensory attributes such as flavour, body and texture, melting characteristics, colour and appearance and total score as well as physical attributes like melting rate and overrun. Based on the output, RSM suggested the rate of addition of strawberry and beetroot powder, stabilizer-emulsifier mixture and sugar to be 4.06 per cent, 0.21 per cent and 15.45 per cent respectively. The experimental frozen yoghurt was prepared as per the suggestions from RSM and compared with control low-fat frozen yoghurt where strawberry and beetroot powder were replaced with strawberry flavour and matching colour. The experimental frozen yoghurt was statistically similar in terms of compositional parameters except moisture and carbohydrate content while the experimental sample was superior to control sample in terms of sensory attributes. Aerobic plate count of both the samples were statistically similar while coliform as well as yeast and mold were absent in the product.